The Level of Religious Literacy Among University Students in Yogyakarta: A Study of Students at UIN Sunan Kalijaga and UGM - Mutmainah, Fatimah Azzahra (UIR Press, 2026)
In recent years, Yogyakarta has been suffered by a series of religious intolerances, an ubiqutious phenomena caused by decrease of religious literacy. By considering the pivotal role of student in maintaning religious harmony, this research, hence, will examine the level of religious literacy among the students of State Islamic University (UIN) Sunan Kalijaga and Gadjah Mada University (UGM) in Yogyakarta. According to experts, religious knowledge alone does not necessarily make someone tolerant. However, this is different from religious literacy, which can foster the development of tolerance. Drawing on those gaps, this research is aimed to analyze the level of religious literacy among the college students in Yogyakarta by using quantitative approach and the method of statistic descriptive. By investigating three main components of religious literacy respectively, religious knowledge, religious multi-interpretation, and religious literacy, I found that the students have different level in each; they occupy the level of ‘quite high’ to ‘high’ for the first variable, ‘low’ to ‘quite high’ for the second and third variable. From the result, I finally argued that the religious literacy does not go in line with the religious knowledge highly accumulated by the students.